PPAR-γ Agonists and Their Effects on IGF-I Receptor Signaling: Implications for Cancer - A. Belfiore; M. Genua; R. Malaguarnera (PPAR Research)
It is now well established that the development and progression of a variety of human malignancies are associated with dysregulated activity of the insulin-like growth factor (IGF) system. In this regard, promising drugs have been developed to target the IGF-I receptor or its ligands. These therapies are limited by the development of insulin resistance and compensatory hyperinsulinemia, which in turn, may stimulate cancer growth. Novel therapeutic approaches are, therefore, required. Synthetic PPAR-γ agonists, such as thiazolidinediones (TZDs), are drugs universally used as antidiabetic agents in patients with type 2 diabetes. In addition of acting as insulin sensitizers, PPAR-γ agonists mediate in vitro and in vivo pleiotropic anticancer effects. At least some of these effects appear to be linked with the downregulation of the IGF system, which is induced by the cross-talk of PPAR-γ agonists with multiple components of the IGF system signaling. As hyperinsulinemia is an emerging cancer risk factor, the insulin lowering action of PPAR-γ agonists may be expected to be also beneficial to reduce cancer development and/or progression. In light of these evidences, TZDs or other PPAR-γ agonists may be exploited in those tumors “addicted” to the IGF signaling and/or in tumors occurring in hyperinsulinemic patients.